Deficits in Visuo-Motor Temporal Integration Impacts Manual Dexterity in Probable Developmental Coordination Disorder - Nobusako, Satoshi; Sakai, Ayami; Tsujimoto, Taeko; Shuto, Takashi; Nishi, Yuki; Asano, Daiki; Furukawa, Emi; Zama, Takuro; Osumi, Michihiro; Shimada, Sotaro; Morioka, Shu; Nakai, Akio (Frontiers in Neurology, 2018)
The neurological basis of developmental coordination disorder is thought to be deficits in the internal model and mirror neuron system in the parietal lobe and cerebellum. However, it is not clear if the visuo-motor temporal integration in the internal model, and automatic-imitation function in the mirror neuron system differs between children with developmental coordination disorder and those with typical development. The current study aimed to investigate these differences. Using the manual dexterity test of the Movement Assessment Battery for Children (2nd edition), the participants were either assigned to the probable developmental coordination disorder group or typical development group. The former was comprised of 29 children with clumsy manual dexterity, while the latter consisted of 42 children with normal manual dexterity. Visuo-motor temporal integration ability and automatic imitation function were measured using the delayed visual feedback detection task and motor interference task, respectively. Further, the current study investigated whether autism spectrum disorder, depressive symptoms, and attention-deficit hyperactivity disorder traits differed among the two groups, since these symptoms are frequent comorbidities of developmental coordination disorder. In addition, correlation and multiple regression analyses were performed to extract factors affecting clumsy manual dexterity. In the results, the delay detection threshold and steepness of the delay detection probability curve, which indicated visuo-motor temporal integration ability, were significantly prolonged and decreased, respectively, in children with probable developmental coordination disorder. The interference effect, which indicated automatic-imitation function, was also significantly reduced in this group. These results highlighted that children with clumsy manual dexterity have deficits in visuo-motor temporal integration and automatic imitation function. There was a significant correlation between manual dexterity, and measures of visuo-motor temporal integration, and attention-deficit hyperactivity disorder traits and autism spectrum disorder. Multiple regression analysis revealed that the delay detection threshold, which indicated visuo-motor temporal integration, was the greatest predictor of poor manual dexterity. The current results supported and provided further evidence for the internal model deficit hypothesis. Further, they suggested a neurorehabilitation technique that improved visuo-motor temporal integration could be therapeutically effective for children with developmental coordination disorder.